Dependência e desequilíbrios entre Montes Claros e as cidades de pequeno porte do Norte de Minas Gerais: Empresas e força de trabalho: Dependence and imbalances between Montes Claros and small cities in the North of Minas Gerais: Companies and the workforce - Cota Pales, Raíssa; Salomão Condé, Eduardo Antônio (Revista Desenvolvimento Social, 2022)
The process of decreased development in large cities, which it has been started in the 1970s, culminated in a reconcentration towards the pole cities. Therefore, several medium-sized cities from Minas Gerais used political incentives for their regional development policy, outstandingly Montes Claros (Norte de Minas). The main effort of this work is to analyze and understand the effects of the process of concentration of development in Montes Claros arising from the reorganization of production in the 1970s and, particularly, from the 1990s, focusing on the role of the State, verifying the consequences, positive and negative, of the polarization of development. The effort was to map the picture referring to the economic potential, showing how the process of re-concentration of development in medium-sized cities, on the one hand, decentralized the development of large metropolises, on the other hand, restricted development to medium-sized cities, leaving the inhabitants of the cities small, as a rule, dependent on the infrastructure of the medium city.